From Village Funds To Frontline Services: Challenges in Implementing the Stunting Policy In Tingkohubu Village - Taufik Harun; Asna Aneta; Dwi Indah Yuliani Sholihin (Universitas Negeri Gorontalo, 2026)
This study examines how Village Fund implementation shapes stunting reduction outcomes at the village level in Indonesia. Using a qualitative case study approach in Tingkohubu Village, the research explores four dimensions of policy implementation: communication, resources, disposition, and bureaucratic structure. Data were collected through in-depth interviews and field observations and analyzed using a mechanism-based approach. The findings indicate that although the Village Fund supports key interventions such as Posyandu services, supplementary feeding, and health education, implementation remains uneven. Communication is largely administrative rather than transformative, resources are available but inadequately distributed, implementers are committed but motivated, and bureaucratic structures are formally established but inconsistently applied. These conditions create a policy-system mismatch, where policy design is not fully aligned with local implementation capacity. This study contributes by demonstrating that stunting reduction outcomes are shaped not only by resource availability but also by the configuration of implementation processes at the frontline service level.